Probing Cosmic Isotropy with the FAST All Sky H i Survey - Yi-Wen Wu; Jun-Qing Xia (The Astrophysical Journal)
This paper leverages the first released catalog from the FAST All Sky H i Survey (FASHI) to examine the hypothesis of cosmic isotropy in the local Universe. Given the design of the overall FAST survey, the inhomogeneous detection sensitivity of FASHI is likely to introduce significant biases in the statistical properties of the catalog. To mitigate the potential influence of spurious clustering effects due to these sensitivity variations, we focus on extragalactic H i sources within the sensitivity range of [0.65, 1.0]. This refined subsample is divided into 10 distinct sky regions, for which we compute the two-point angular correlation functions (2PACF) over angular scales of 0 $\mathop{.}\limits^{\unicode{x000b0}}$ 5 <  θ  < 10°. We apply the Markov Chain Monte Carlo method to fit these 2PACFs with a power-law model and assess the statistical significance of the best-fit parameters for the 10 FASHI sky regions by comparing them against results from mock catalogs generated under the assumptions of homogeneity and isotropy. Our findings indicate that the local Universe, as traced by the H i sources in the FASHI survey, aligns with the cosmic isotropy hypothesis within a 2 σ confidence level. We do not detect any statistically significant deviations from cosmic isotropy in the FASHI survey data.